Bullous aplasia cutis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Congenital bullous aplasia cutis is a well-known subtype of aplasia cutis. Its clinical features correspond to its histological findings, that are characterized by edematous dermis with isolated stellate cells supplied with subtle cytoplasmic extensions and sometimes with small cyst-like spaces delimited by spindle cells (1). Some Authors (2), taking into account the clinical and histological findings, suggested that this subtype of aplasia cutis represents a minor form of neural tube defect, somehow reminiscent of meningocele. The initial cystic or blister-like lesions turn slowly in the following months into scarring plaques completely superimposable to typical congenital aplasia cutis.